2018
DOI: 10.1186/s12888-018-1781-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of antepartum depressive and anxiety symptoms in expectant mothers and fathers: results from a perinatal psychiatric morbidity cohort study in the east and west coasts of Malaysia

Abstract: BackgroundResearch on antepartum psychiatric morbidities investigating depressive and anxiety symptoms in expectant mothers and fathers is lacking in low- and middle-income countries. This study aimed to estimate the prevalence of antepartum depressive, anxiety and co-occurring significant symptoms and explore the associated factors in a cross-section of Malaysian expectant mothers and fathers.MethodsWe used cross-sectional data from a prospective cohort study of 911 expectant mothers and 587 expectant fathers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 45 publications
4
45
1
5
Order By: Relevance
“…Such figures are extremely relevant, especially if we consider that the highest possible threshold reported in the literature (i.e., 13 or above) has been used as the cut-off value for depression in the current study. When anxiety and depressive symptoms are compared, this study confirms that anxiety is usually more prevalent than depression among expectant mothers as already found in previous studies (Nasreen et al, 2018;van de Loo et al, 2018). However, while depression and anxiety symptoms are quite common among pregnant and postpartum women, the women in our sample were significantly more at risk for developing anxiety and depressive symptoms; these findings suggest that the pandemic and the measures adopted to fight its spread have had a negative impact on expectant and postpartum women' well-being, thus constituting an additional risk factor for this specific population.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Such figures are extremely relevant, especially if we consider that the highest possible threshold reported in the literature (i.e., 13 or above) has been used as the cut-off value for depression in the current study. When anxiety and depressive symptoms are compared, this study confirms that anxiety is usually more prevalent than depression among expectant mothers as already found in previous studies (Nasreen et al, 2018;van de Loo et al, 2018). However, while depression and anxiety symptoms are quite common among pregnant and postpartum women, the women in our sample were significantly more at risk for developing anxiety and depressive symptoms; these findings suggest that the pandemic and the measures adopted to fight its spread have had a negative impact on expectant and postpartum women' well-being, thus constituting an additional risk factor for this specific population.…”
Section: Discussionsupporting
confidence: 90%
“…Previous research on pregnant women has extensively studied the impact and prevalence of antenatal anxiety and depression reporting high rates of such conditions across various countries (Biaggi et al, 2016;Falah-Hassani et al, 2017;Nasreen et al, 2018;van de Loo et al, 2018). In this respect, although differences have been reported across studies due to the methodological approaches used, the prevalence of anxiety disorders among pregnant women has been found to be approximately 15% (Dennis et al, 2017).…”
Section: Psychological Well-being Of Expectant Mothersmentioning
confidence: 99%
“…Mental health problems during pregnancy have been reported to have detrimental consequences on the woman and her foetus (Field 2011;Rees et al 2019). Depression and anxiety are the most reported mental health problems among pregnant women (Nasreen et al 2018). The prevalence rate of depression among pregnant women of low-and lower-middle-income countries has been estimated to be 15.6% (Fisher et al 2012).…”
mentioning
confidence: 99%
“…This usually occurs with other mental health problems and stressors or poor relationship quality with close family members including husbands (Johnson et al 2018). Although these previous studies mainly focused on pregnant women, few studies have simultaneously explored fathers' mental health when their wives are pregnant (Nasreen et al 2018;Wee et al 2011). Studies have shown that poor couple interaction or poor relationship quality also affects their mental health, such as anxiety or depression symptoms during pregnancy (Figueiredo et al 2018;Røsand et al 2012).…”
mentioning
confidence: 99%
“…A valid Malay version of DASS-21 will be used in current study [16]. DASS-21 has been applied in past studies involving pregnant Asian women, including Malaysian pregnant women [17,31].…”
Section: Depression Anxiety and Stress Scales (Dass-21) Questionnairementioning
confidence: 99%